2008
DOI: 10.1080/02786820802339553
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar Charging of Fine and Ultra-Fine Particles Using Carbon Fiber Ionizers

Abstract: A simple and novel unipolar charger using carbon fiber ionizers was developed to effectively charge fine and ultra-fine aerosol particles without the generation of ozone. The particle penetration in the charger was investigated for non-charged, neutralized, and singly charged particles in the size range of 20-200 nm. Particle loss and the intrinsic, exit and extrinsic charging efficiencies of fine and ultra-fine particles were also investigated for non-charged particles at different applied voltages to the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…3 , and these values were much higher than the corresponding values of approximately 10 12 s m -3 generated by ionizers (Han et al, 2008). Therefore, we can expect the charging efficiency and consequent collection efficiency using a corona discharge to be much higher than those using an ionizer are.…”
Section: Voltage-current Characteristicsmentioning
confidence: 65%
“…3 , and these values were much higher than the corresponding values of approximately 10 12 s m -3 generated by ionizers (Han et al, 2008). Therefore, we can expect the charging efficiency and consequent collection efficiency using a corona discharge to be much higher than those using an ionizer are.…”
Section: Voltage-current Characteristicsmentioning
confidence: 65%
“…We measured the sizes of the bioaerosol particles and found that they most frequently had the same size as the GSE particles . To determine whether the use of air ions on the test filters had an antimicrobial effect, ions were supplied to the filter surface by a carbon fiber ionizer (Han et al, 2008) with a DC power supply and 1 L min -1 of filtered air during 5 minutes, as shown in Fig. 2(c) after exposing the filter to S. aureus.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, filters were coated with GSE particles and air ions were also prepared (Han et al, 2008) and injected onto the filter surface. Simply immersing the filter media in the GSE solution can cause a significant pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…For the same level of ionization, a carbon fiber ionizer typically requires lower voltage than metallic cathodes of corona discharge because the diameter of carbon fibers is much smaller (about 5-10 mm) than that of metallic cathodes. Lower voltage applied to carbon fibers is sufficient to trigger ionization at the tip of carbon fiber cathodes; while, the electric field from the applied voltage is not high enough to induce unnecessary ozone reactions (shown in Equations (6) and (7)) (Han et al 2008;Han et al 2009). This may explain the negligible ozone emissions by AC3 and AC4.…”
Section: ¡1mentioning
confidence: 99%